Quest and designing of organic molecular frameworks for efficient hole transport materials - Priya Singh; Aditya Kumar; Ajeet Singh (Chemistry of Inorganic Materials)
Azaborine derivatives were investigated as hole-transporting materials (HTMs) by employing density functional theory (DFT) calculations. Marcus theory and Einstein relationship have also been used to investigate different properties of HTMs. We have also performed time-dependant density functional theory (TD-DFT) calculations to investigate the optical, electronic and charge transport properties of designed molecules. Calculated results infer that the designed molecules display characteristic traits of a HTM. The calculated highest occupied molecular orbital (HOMO) level and hole reorganization energies are lower than that of electronic ones. Further, molecular electrostatic potential analysis and density of states are used to identify the various charge locations in molecules. To check the viability of our designed HTMs, we have taken 9:PC61BM complex for better understanding the charge transfer between the hole transport materials with well-known electron acceptor material.